2020
DOI: 10.1186/s41687-020-0184-4
|View full text |Cite
|
Sign up to set email alerts
|

A cohort study of quality of life in partners of young breast cancer survivors compared to partners of healthy controls

Abstract: Background: Partners of young breast cancer survivors (BCS) are at increased risk for deficits in quality of life (QoL). To intervene effectively, it is important to understand how the breast cancer experience impacts partners. The purpose of this study was to compare QoL between partners of young BCS and partners of healthy acquaintance controls. Methods: Partners of young BCS (3-8 years post treatment and ≤ 45 years old at diagnosis) and partners of agematched healthy acquaintance controls completed question… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 49 publications
0
5
2
Order By: Relevance
“…[ 31 ] In a study on breast cancer, lack of spousal intimacy was also a factor related to the quality of life after breast cancer surgery. [ 32 ] The results of this study are significantly higher than those of the above scholars. This may be related to the location of the CRC and stoma in this study.…”
Section: Discussioncontrasting
confidence: 65%
See 1 more Smart Citation
“…[ 31 ] In a study on breast cancer, lack of spousal intimacy was also a factor related to the quality of life after breast cancer surgery. [ 32 ] The results of this study are significantly higher than those of the above scholars. This may be related to the location of the CRC and stoma in this study.…”
Section: Discussioncontrasting
confidence: 65%
“…In the study by Manne et al, 21.6% of the spouses of prostate cancer patients expressed dissatisfaction with their couple intimacy [31] . In a study on breast cancer, lack of spousal intimacy was also a factor related to the quality of life after breast cancer surgery [32] . The results of this study are significantly higher than those of the above scholars.…”
Section: Discussioncontrasting
confidence: 51%
“…Furthermore, in another qualitative study in the Iranian context, men’s sexual desire decreased mostly due to mastectomy and treatment complications such as alopecia [ 31 ]. A cohort study revealed that the partners of young BC survivors had more sexual difficulties and less sexual enjoyment compared to the partners of healthy controls [ 42 ]. Undesirable sexual functions have been reported in studies on the sexual issues of women with BC.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, they report poorer quality of life and well-being than other caregiver populations [22][23][24][25]. Partners of BCS indicate more quality of life problems than partners of healthy women up to 14 years after diagnosis and treatment [26], are at increased risk of being hospitalized with an affective disorder [27], and are more likely to use antidepressant medication [28].…”
Section: Introductionmentioning
confidence: 99%